Mentally disordered offenders discharged from designated hospital facilities under the medical treatment and supervision act in Japan: Reoffending and readmission. (5th July 2019) - Nagata, Takako; Tachimori, Hisateru; Nishinaka, Hirofumi; Takeda, Koji; Matsuda, Taro; Hirabayashi, Naotsugu
Abstract: Background: Current Japanese forensic mental health legislation (Medical Treatment and Supervision Act [MTSA]) was enacted in 2003. Little is known, however, about the actual outcomes for the offender patients detained within hospitals under this provision. Aim: This study aimed to quantify reoffending and readmission following patients' discharge from forensic psychiatric hospital units across Japan and explore related risk factors. Methods: We followed up 526 offenders with mental disorder who had been detained under the MTSA and who were subsequently discharged from any of the 28 hospitals nationwide between 2007 and 2015. Results: The total cumulative reoffence rate was found to be 2.5% (1.1–3.9%) after 1 year and 7.5% (4.6–10.4%) after 3 years. The rate of serious reoffending was 0.4% (−0.18% to 0.99%) after 1 year and 2.0% (0.4–3.6%) after 3 years. The cumulative admission rate to local psychiatric hospitals following a discharge was 21.8% after 6 months and 37.6% after 1 year. Patients who had been discharged from their MTSA order but transferred to a general psychiatric hospital before open community residence—because it was necessary to build community supports—were more likely to reoffend than those discharged directly to the community. Patients who had been diagnosed with a substance use disorder (F10–F19) and had one subsequent admission were at higher risk of further readmissions. Conclusions: The low reoffending rates could be attributed to the intensive treatment and care plans required by the MTSA. The high rate of readmission to psychiatric hospitals may indicate shortcomings in community mental health services in Japan.